Science communication is integral to attracting widespread participation in bushfire recovery citizen science - Roger, Erin; Kinsela, Andrew S. (Frontiers in Environmental Science, 2023)
The 2019/20 bushfire season was a catastrophic event affecting large areas of Australia. Due to the devastating impact on biodiversity, the Australian public wanted to contribute towards assessing the impact of this disaster. To address this, three citizen science projects were established to engage citizen scientists in various aspects of environmental recovery. The projects offered different ways of participating, ranging from online, through to community field events, including those requiring specialised localised knowledge. As a result, communication approaches targeting different audiences were required. Here, we detail the communication strategies employed to promote and engage a diverse national and global audience in bushfire recovery projects. We provide metrics and analysis on how and where we promoted projects, including a breakdown of participation numbers for each project. We detail lessons learnt, and how we would improve our communication approach for future disaster recovery events to increase awareness at a community level and more broadly. Despite numerous challenges, including organising public-facing events during a global pandemic, the program serves as an exemplar of how to successfully partner with communities, research teams and government to enable citizen scientists to make meaningful, valuable and timely contributions to research. Ultimately, the program enabled widespread community involvement in bushfire recovery and filled gaps in baseline and post-fire data.